Patient's perspective on long‐term complications after superficial parotidectomy for benign lesions: Prospective analysis of a 2‐year follow‐up. (22nd April 2018) - Wolber, P.; Volk, G.F.; Horstmann, L.; Finkensieper, M.; Shabli, S.; Wittekindt, C.; Klussmann, J.P.; Guntinas‐Lichius, O.; Beutner, D.; Grosheva, M.
Abstract : Objective: Evaluation of patients′ perspective on long‐term complications after superficial parotidectomy for benign lesions. Design: A prospective nonrandomized controlled multicenter study. Setting: Three university‐based tertiary referral centers (Departments of Otorhinolaryngology of Cologne, Jena and Giessen; all in Germany). Participants: 130 adult patients, who underwent a primary superficial parotidectomy for benign tumors of the parotid gland, were consecutively included from 09/2010 to 05/2012. 61 patients completed every follow‐up examination. Main outcome measures: Complications were evaluated using the validated German‐language questionnaire Parotidectomy Outcome Inventory 8 at six, 12 and 24 months after surgery. Pain intensity was assessed on a numeric rating scale (NRS) at each follow‐up visit. Results: At 6 months after surgery, 90% characterized hypoesthesia as the most disturbing problem, followed by fear of revision surgery (57%) and scar (56%). Facial palsy (14%) posed the minor problem. Hypoesthesia improved significantly during the follow‐up period (all P  < .05), but still posed a problem for 78% of the patients after 2 years. Pain, which initially bothered 53% of the patients, significantly decreased, whereas impairment due to Frey′s syndrome significantly increased during the follow‐up (6 vs 24 months; P  = .002 and P  = .001, respectively). Scar, substance loss, xerostomia, facial palsy, and anxiety affected patients with unvarying severity during the 2 years (all P  > .05). Conclusions: From patients′ perspective, sensation loss posed the major subjective problem after superficial parotidectomy. Appearance of the scar, and fear of revision surgery impaired more than 50% of the patients in their daily life without significant improvement during the 2 years postoperatively. Although superficial parotidectomy is a highly standardized and safe procedure, limited parotidectomy for proven benign parotid salivary gland neoplasms is more likely to result in patients with minimal or no displeasing complications.